Genetic Bases of Orthodontics: A Review - Kadhom, Zainab Mousa (Scientific Journal of Medical Research, 2021)
Objectives: This review aimed to show the genetic components of malocclusion and craniofacial disorders to assist in understanding the causes of the presence of a particular occlusion or dentofacial anomalies in some patients and considering genetic factors as an important element to diagnose the dentofacial disturbances and the malocclusion of genetic origin. Conclusion: The genetics parts in orthodontics should be considered to recognize the reasons for certain occlusion in some individuals. Furthermore, detecting a genetic component’s role in most dental anomalies and malocclusions is very challenging because of its polygenic nature.